Developing Interpersonal Skills and Professional Behaviors through Extracurricular Activities Participation: a Perception of King Abdulaziz University Medical Students - Awatif A. Jamal, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Extracurricular activities are activities performed by students which fall outside a school or university academic curriculum. Students from primary schools to tertiary educational institutes voluntarily participate in ECAs. These activities are organized and directed by various students associations and divisions under faculty sponsorship. This study investigated undergraduate medical students perceptions regarding interpersonal skills and professional behaviors gained by participating in numerous extracurricular activities. It further discusses factors within ECAs which promotes developments and explores facilitation that are missing while increasing students participation. Semi-structured interviews were conducted with nine medical students who participated in King Abdulaziz University's Students Day Activity. The interviews were transcribed and analyzed by the author using the grounded theory. The participants acknowledged the gain of many interpersonal skills such as communication and managerial skills, teamwork, problem solving, leadership and self-reflection. They affirmed that exposure to various situations taught them respect, sharing, accepting responsibilities and confidence, which greatly coached their professional behaviors and positively influenced their academic work. In conclusion, ECAs promoted a holistic approach to learning and teaching. The findings confirmed that participation in ECAs promoted the gain of interpersonal skills and professional behaviors in medical students at King Abdulaziz University, Jeddah, Saudi Arabia.